Капиллярные волны при коалесценции микрокапель со слоем жидкости; Теплофизика и аэромеханика; Т. 22, № 4 - Федорец А. А. Александр Анатольевич; Марчук И. В. Игорь Владимирович; Стрижак П. А. Павел Александрович; Кабов О. А. Олег Александрович (2015, 2015)
Заглавие с экрана